KELAYAKAN KARYA TULIS PENULIS CILIK SEBAGAI BAHAN AJAR BAHASA INGGRIS - Anita Anggraeni; Cynantia Rachmijati (STKIP Siliwangi, 2015)
In foreign language context, English is taught mostly in classroom. Providing a lot of exposures should be considered by the teachers. Textbook is one of the way canbe used in the process of teaching-learning English. This study aims to investigatethe strategies used by the teacher when she or he choose an appropriate and idealtext book which is fit in with thr situation and condition of the student. To collectthe data, the researcher make same analysis to 20 books title “Kecil Kecil PunyaKarya” (KKPK) and make some interviews with the writer and the readers of thesebooks. The findings revealed that this book effective as a part of textbook we used inthe classroom. This study indicated that there some improvements of students`English ability in terms of quality such as effectiveness, content, vocabulary. Therespondents said that the love this textbook because the story is the reflection oftheir life. And it makes the interesting to read it. The research shows that KKPKinclude in the category of “appropriate” and “almost appropriate”, with the lowestpercentage 53,57 % dan the highest percentage 76,19%. So we can conclude thatteacher can use KKPK as one of the English textbook in the classroom.